Upper gastrointestinal bacillary angiomatosis causing hematemesis: a case report. - Chetty, R; Sabaratnam, R (2003)
A 38-year-old HIV-positive woman presented with massive hematemesis on initial admission to hospital. Endoscopy revealed ulcerated nodular lesions in the esophagus, stomach, and duodenum. The clinical impression was of Kaposi's sarcoma. The stomach was biopsied when the patient re-presented, and another endoscopy was performed. The biopsy showed mucosal ulceration with a proliferation of vascular channels associated with neutrophils and clumps of purplish, granular bacterial colonies, which were highlighted by a Warthin-Starry stain. The histopathological features were typical of bacillary angiomatosis. This case highlights bacillary angiomatosis involving the gastrointestinal tract at multiple sites, the cause of massive upper gastrointestinal hemorrhage that was the initial presentation of an HIV-positive patient, and the occurrence of visceral bacillary angiomatosis in the absence of cutaneous lesions.